Non-occlusive mesenteric ischemia during acute stroke management: three case reports - Kazuki Fujii; Tadahiko Seki; Yasuyuki Nakata; Kazuaki Atagi; Takeshi Matsuyama (Surgical Case Reports)
Abstract Background There are many reports of non-occlusive mesenteric ischemia in patients on maintenance hemodialysis and following cardiac surgery. However, there are few reports of non-occlusive mesenteric ischemia in patients with acute stroke. Case presentation We report three cases of non-occlusive mesenteric ischemia with onset during treatment for acute stroke. All of the patients were undergoing strict blood-pressure control, and two patients developed NOMI soon after tracheostomy when enteral nutrition had been resumed. Conclusion Many stroke patients are older adults with risk factors such as arteriosclerosis. Thus, during acute stroke management, there is a possibility that patients may develop non-occlusive mesenteric ischemia due to decreased intestinal blood flow secondary to strict blood-pressure control. This case report implicates early enteral nutrition as a potential etiopathogenic factor of non-occlusive mesenteric ischemia in patients with acute stroke.